Adaptation to high salt concentrations in halotolerant/halophilic fungi: a molecular perspective - Plemenitaš, Ana; Lenassi, Metka; Konte, Tilen; Kejžar, Anja; Zajc, Janja; Gostinčar, Cene; Gunde-Cimerman, Nina (Frontiers in Microbiology, 2014)
Molecular studies of salt tolerance of eukaryotic microorganisms have until recently been limited to the baker’s yeast Saccharomyces cerevisiae and a few other moderately halotolerant yeast. Discovery of the extremely halotolerant and adaptable fungus Hortaea werneckii and the obligate halophile Wallemia ichthyophaga introduced two new model organisms into studies on the mechanisms of salt tolerance in eukaryotes. H. werneckii is unique in its adaptability to fluctuations in salt concentrations, as it can grow without NaCl as well as in the presence of up to 5 M NaCl. On the other hand, W. ichthyophaga requires at least 1.5 M NaCl for growth, but also grows in up to 5 M NaCl. Our studies have revealed the novel and intricate molecular mechanisms used by these fungi to combat high salt concentrations, which differ in many aspects between the extremely halotolerant H. werneckii and the halophilic W. ichthyophaga. Specifically, the high osmolarity glycerol signalling pathway that is important for sensing and responding to increased salt concentrations is here compared between H. werneckii and W. ichthyophaga. In both of these fungi, the key signalling components are conserved, but there are structural and regulation differences between these pathways in H. werneckii and W. ichthyophaga. We also address differences that have been revealed from analysis of their newly sequenced genomes. The most striking characteristics associated with H. werneckii are the large genetic redundancy, the expansion of genes encoding metal cation transporters, and a relatively recent whole genome duplication. In contrast, the genome of W. ichthyophaga is very compact, as only 4,884 protein-coding genes are predicted, which cover almost three quarters of the sequence. Importantly, there has been a significant increase in their hydrophobins, cell-wall proteins that have multiple cellular functions.